32 Improving patient and public involvement in end of life care research. Issue 3 (1st September 2017) - Seddon, Kathy; Murray, Alexandra; Buckle, Peter
Abstract : Introduction: Members of the Marie Curie (MC) Expert Voices Group (EVG) have all cared for someone at the end of life. Research EVG (REVG) members use this experience to contribute to research. To improve Patient and Public Involvement (PPI) in end of life research they used motivation theory to review case studies of their contributions Aim(s): To improve the quality of PPI in end of life care (EOLC) research through consideration of motivation, using REVG case studies. Method(s): Review case studies of REVG involvement in EOLC research. Note factors contributing to participant sense of efficacy. Explore alignment with participant professed reasons for contributing to research thus draw together key factors promoting successful PPI. Results: Case Studies of REVG involvement at all stages of research cycles included: Reviewing research submissions e.g. Research Centre QQR Questionnaire design and wording e.g. Delphi study on advance care planning Consensus days e.g. Bereavement consensus days Dissemination e.g. Presentations to government. Brain Tumour information sheet Impact e.g. Use of case studies for review publications Factors found to contribute to participant sense of efficacy in these examples included: Targeted informative invitations Clear jargon free instructions Good facilitation drawing out participant experiences Ensuring alignment with participant's reasons for action included: Opportunities to use all expertise Understanding the range of participant goals and planning to allow them to be met Conclusion(s): PPI may be more effective if participant motivational needs are understood and planned for. References: . Bandura, A. (1993). Perceived self-efficacy in cognitive development and functioning. Educational Psychologist, 28, 117–148. . Csikszentmihalyi, M. (1997b). Finding flow. New York: Basic Books. . de Charms, R. (1976). Enhancing motivation. New York: Irvington. . Deci, E. L. (1980). The psychology of self-determination. Lexington MA: D. C. Heath. . Maslow, A. H. (1968). Towards a psychology of being. New York: Van Nostrand-Rheinhold. . Yin, R. (1994). Case study research: Design and methods (2nd edn.). Thousand Oaks, CA: Sage Publishing.